Wrapping and unwrapping material culture
1 online resource (245 pages)
Keywords: "This innovative volume challenges contemporary views on material culture by exploring the relationship between wrapping materials and practices and the objects, bodies, and places that define them. Using examples as diverse as Egyptian mummies, Celtic tombs, Native American ceremonial bundles, baby swaddling, and contemporary African textiles, the dozen archaeologist and anthropologist contributors show how acts of wrapping and unwrapping are embedded in beliefs and thoughts of a particular time and place. These context specific, cultural, and technical acts offer a new lens on material culture and its relationship to cultural meaning"--